Performance, carcass, and meat traits of different cattle types - Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1979)
Different crossbred (X) cattle types were evaluated for growth, feed efficiency, carcass and meat traits. Steers were studied from mating Angus (A), Hereford (H), Brahman (B), Sahiwal (S), Pinzgauer (P), and Tarentaise (T) sires to Angus and Hereford females.
Keywords: Cattlemen' s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Performance; Carcass; Meat traits